Hyvän elementit ammatillisen koulutuksen johtajuudessa ja rehtorin työssä - Hänninen, Riitta (2009)
This inductive study focuses on the elements of the good in leadership in the field of vocational education. Nine 'Principals of the Year', nominated by the Vocational Principals' Organisation in 1994-2002, wrote down their thoughts on five themes about their work and thinking. The writings were analysed using Glaser's inductive grounded theory and hermeneutical reading. The process progressed from seven categories of open (substantive) coding into five categories of theoretical coding concerning principals' work, and further into three main categories of selective coding, i.e. responsibility, power and caring. The process of Glaserian inductive approach produces a substantive theory, which in this study suggests that the elements of the good in principals' work are epistemic, existential, and ethical connections of responsibility, the content of the main categories. The core category of this study is humanity. The good is hiding in principals' many actions. We can also find it inside the connections between the elements of the good. On the borders of the main categories the connections of the concepts with humanity build a strong quality investment such as expertise knowhow, ethical culture and a moral way of action, and communal trust. The main part of this formulated theory builds on the elements of the good, and thus the substantive theory can be described as an ideal model of good leadership in the field of vocational education. The principals implement it according to their own humanity and expertise. The substantive theory emphasizes the communal aspect and it has many similarities with the studies and articles about authentic leadership. School communities and their leaders could use the content of the substantive theory as material in their self-assessment processes.